Implementation of Artificial Intelligence in Governance: Potentials and Challenges - Rahmat Salam; Marja Sinurat; Izzatussolekha; Akhmad Yasin; Rian Sacipto (Global Writing Academica Researching and Publishing, 2023)
One industry that uses technology based on artificial intelligence in its operations is the government sector. Applying artificial intelligence in government settings can offer significant opportunities, but doing so comes with several obstacles that must be conquered first. Despite these obstacles, the application of AI in government settings can offer substantial possibilities. This article addresses the potential and challenges of integrating artificial intelligence in government and presents ideas to solve these challenges. The report also provides some background information on artificial intelligence. A qualitative technique combined with descriptive methodologies was used for this investigation. According to the findings of this investigation, the application of artificial intelligence in government settings carries with it a significant possibility of enhancing the quality of public services, improving the quality of decisions made, and enhancing the transparency and accountability of government operations. Nevertheless, some obstacles need to be conquered, such as concerns about protecting one's privacy and data, as well as worries regarding making decisions that are not fair.